2018
DOI: 10.1021/acsami.8b09513
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemistry Controls Anomalous Ferroelectric Behavior in Lithium Niobate

Abstract: Polarization switching in ferroelectric materials underpins a multitude of applications ranging from nonvolatile memories to data storage to ferroelectric lithography. While traditionally considered to be a functionality of the material only, basic theoretical considerations suggest that switching is expected to be intrinsically linked to changes in the electrochemical state of the surface. Hence, the properties and dynamics of the screening charges can affect or control the switching dynamics. Despite being r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…[33][34][35][36] Near-ambient pressure X-ray photoelectron spectroscopy (AP-XPS), allowing the contributions of H 2 O and OH − groups to be considered separately, 15,17,37 has corroborated these observations, demonstrating an asymmetric adsorption of the charged species as a function of polarization orientation. 35,36 More recently, the combination of SPM with secondary ion mass spectrometry 38 has suggested that the evolution of chemical states during polarization switching, beside changes in surface chemistry, 39 can also include redistribution of bulk cations. 28,40 However, both the SPM and AP-XPS approaches present some inherent challenges, which can make a fully quantitative analysis of the interaction of water with ferroelectrics difficult.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36] Near-ambient pressure X-ray photoelectron spectroscopy (AP-XPS), allowing the contributions of H 2 O and OH − groups to be considered separately, 15,17,37 has corroborated these observations, demonstrating an asymmetric adsorption of the charged species as a function of polarization orientation. 35,36 More recently, the combination of SPM with secondary ion mass spectrometry 38 has suggested that the evolution of chemical states during polarization switching, beside changes in surface chemistry, 39 can also include redistribution of bulk cations. 28,40 However, both the SPM and AP-XPS approaches present some inherent challenges, which can make a fully quantitative analysis of the interaction of water with ferroelectrics difficult.…”
Section: Introductionmentioning
confidence: 99%
“…39 In a next step, we analyze spatially varying cKPFM response measured on macroscopically pre-poled lithium niobate (LN) that is subject to strong electrostatic interactions typical for that ferroelectric material. 10 To further corroborate the applicability of our analysis approach we process cKPFM response measured across the ferroelectricrelaxor phase transition on multiple grains of lanthanum zirconate titanate (PLZT), which even in the ferroelectric state exhibits peculiarities in hysteresis loop, as commonly observed for relaxors. 31 Fig.…”
Section: Resultsmentioning
confidence: 88%
“…The classication as ferroelectric switching or electrostatically driven artefacts, which is oen the main reason to apply this technique, has been only vaguely and qualitatively dened as the presence/ absence of formation of "two bands" and the cKPFM curve shapes resembling a hysteresis loop, as opposed to electrostatic artefacts which would appear as one band of straight lines. 10,39 Such an assignment is highly dependent on the probing versus writing voltage ratios, as well as the vagueness of the denition of a "good" hysteresis loop.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations